Assessing the Influence of Renewable Energy Consumption and Domestic Investment on Environmental Quality in Somalia - Abdi Dhiif, Abdirahman; Sheikh Ali, Ali Yassin (International Journal of Energy Economics and Policy, 2025)
Environmental sustainability is a critical global issue, prompting initiatives to diminish emissions and alleviate the effects of climate change. This study examines the impact of renewable energy consumption and domestic investment on the environmental quality of Somalia from 1990 to 2020. The study used econometric methods, including the Pairwise Granger Causality Test and the ARDL model, to ascertain substantial correlations between environmental quality and variables such as population growth, renewable energy utilization, domestic investment, and economic growth. Research indicates a sustained positive link between population increase and environmental quality, but renewable energy utilization, domestic investment, and economic growth have a negative correlation with environmental quality. This research provides critical insights for policymakers in Somalia and beyond, highlighting the necessity of improving energy efficiency and decreasing emissions via investments in clean energy.